Assessing business models for the local food market in the Pacific Northwest - Patterson, Christopher L. (Kansas State University, 2016)
Local foods is a growing market segment, and there are multiple businesses attempting to capitalize on the interest in buying from local producers. As consumer interest in local food continues to grow, businesses will be created to meet a growing demand. This research identifies areas in current customer segments in local foods that are not being serviced or are being underserviced. Potential business models are then identified in order to service the identified customer segments. One primary service gap that was identified in the research was that end consumers were not able to purchase local food per their definition of local food. Major retailers sell local produce and food items that were grown within the state boundaries, but few sell produce that is grown within the community. A cost/revenue framework simulation was built to compare three different types of business models that could potentially fill the identified service gap in the target area of Washington State. After the simulation was performed, the models were compared on net present values in lowest feasible, expected, and best case scenarios. Factors such as imitability and scalability were also considered. The three models were a micro-farming app and website, a CSA delivery and management service, and a non-profit community garden. The micro-farming site and app would allow producers and artisans, no matter the scale, to have an online marketplace to sell and trade food products. The CSA management and delivery model delivers CSA shares to customers while charging a delivery and management fee to the farm on which the CSA is based. The non-profit community garden is a five-acre parcel with a water retention system and offers tiered services for garden management in King County. Results suggest that even though each business model could potentially be feasible in the targeted areas, the most visibly promising model was the micro-farming website and app. Beyond the financial overview and analysis reported in the thesis, the business models could be ranked in a variety of ways according to an entrepreneur’s interest. More importantly, there is no better time than now to start building a business model that services customer’s interest in local food.
Keywords: Local Food; Strategic Map; Pacific Northwest; Business Ideation; Logistics; Business Feasibility